Pengaruh Kepercayaan dan Peran Supervisor Terhadap Turnover Intention Pada PT. Graha Mandiri Barata Medan - Maha, Muhammad Faisal; Bagus Handoko; Muller Tamba (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2023)
Abstract This study aims to determine the effect of organizational trust and the role of supervisors on turnover intention at PT. Graha Mandiri Barata Medan. The population in this study amounted to 285 people, with a total sample size of 74 advisors on turnover intention at PT. Graha Mandiri Barata Medan. The population in this study amounted to 285 people, with a total sample size of 74. The sampling method is random sampling. The data obtained was then processed using SPSS Statistics version 22. Data analysis techniques in this study included reliability tests, validity tests, classical assumption tests (multicollinearity tests, normality tests, and heteroscedasticity tests), statistical tests (coefficient of determination test (R2)), individual parameter significance tests (t tests), and simultaneous significance tests (f tests). The results showed that organizational trust has a positive and significant effect on turnover intentions. The supervisor's role has a positive and significant effect on turnover intentions. Organizational trust and the supervisor's role influence each other significantly in turnover intentions.